2020
DOI: 10.3390/insects12010018
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Efficacy of Diatomaceous Earth, Household Soaps, and Neem Oil against Spodoptera frugiperda (Lepidoptera: Noctuidae) Larvae in Benin

Abstract: Spodoptera frugiperda was first reported in Africa in 2016 and has since become a serious threat to maize/cereal production on the continent. Current control of the pest relies on synthetic chemical insecticides, which can negatively impact the environment and promote the development of resistance when used indiscriminately. Therefore, great attention is being paid to the development of safer alternatives. In this study, several biorational products and a semi-synthetic insecticide were evaluated. Two househol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 63 publications
2
8
0
Order By: Relevance
“…Among all the treatments highest per cent reduction of chickpea pod borer as well as increasing the yield was recorded in T 5 (74.41%). Similar findings made by Zeni et al [10],Constanski et al [11], Aniwanou et al [12]. T 6 (73.26%) is found to be the next best treatment which is in line with the findings of Sabbour et al [13], Arooni-Hesari et al [14].…”
Section: Second Spraysupporting
confidence: 89%
“…Among all the treatments highest per cent reduction of chickpea pod borer as well as increasing the yield was recorded in T 5 (74.41%). Similar findings made by Zeni et al [10],Constanski et al [11], Aniwanou et al [12]. T 6 (73.26%) is found to be the next best treatment which is in line with the findings of Sabbour et al [13], Arooni-Hesari et al [14].…”
Section: Second Spraysupporting
confidence: 89%
“…Heavy rain forces FAW larvae out of the whorl, so the efficiency of hand picking may be increased by conducting it immediately after heavy showers. Preliminary results for soil, sand, ash, and soapy water are mixed, suggesting specific characteristics of the materials or their application are important (Babendreier et al 2020;Aniwanou et al 2021;Varma et al 2021). Ash is an unconventional pesticide that acts as a physical poison causing abrasion of insect cuticle, thus exposing pests to death through desiccation.…”
Section: Other Interventionsmentioning
confidence: 99%
“…More specifically, Sisay et al (2019), showed in both laboratory and field trials, the efficacy of wettable powder of neem seed (applied in 5% water) against S. frugiperda. Likewise, Neem oil has also been reported by several other authors as effective in controlling S. frugiperda (Adeye et al, 2018;Duarte et al, 2019;Phambala et al, 2020;Aniwanou et al, 2021). The efficacy of Neem extracts on S. frugiperda and other insect pest species is linked to its biochemical composition that includes substances toxic to the targeted pests (Medina et al, 2003;Rakshit et al, 2008;Li et al, 2010;Insanu et al, 2013;Dono et al, 2020).…”
Section: Discussionmentioning
confidence: 77%
“…Indeed, although the maize yield increase is relatively higher with Emacot 19 EC than in the biopesticide treatments, this gain may not significantly differ from those obtained with Neem oil and Jatropha oil. Similarly, several authors have also reported yield increase of many crops treated with Neem or Jatropha oil to control insect pests (Diabaté et al, 2014a;Kammo et al, 2019;Aniwanou et al, 2021).…”
Section: Discussionmentioning
confidence: 91%